2016
DOI: 10.1111/sms.12745
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resistance training on phase angle in older women: A randomized controlled trial

Abstract: Phase angle (PhA) is an angular-derived bioelectrical impedance parameter based on resistance and reactance that has been widely used in different populations as an objective indicator of cellular health. The purpose of this study was to analyze the effect of resistance training (RT) on PhA in older women. Forty-one older women (67.2 ± 4.5 years, 64.0 ± 12.3 kg, 154.7 ± 5.2 cm, and 26.6 ± 4.8 kg/m ) were randomly assigned to one of two groups: a training group (TG, n = 19) that underwent progressive RT for 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
60
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 47 publications
(67 reference statements)
11
60
1
Order By: Relevance
“…Previous findings from our laboratory with a different cohort of older adult women, 25 as well as other findings in the literature, have already shown that the PhA can be improved by RT. 26,41 Previous studies also have observed an improvement in inflammatory markers after RT in the same magnitude as reported by Onable-Pearson 24 for TNF-α and Tomeleri et al for IL-6.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Previous findings from our laboratory with a different cohort of older adult women, 25 as well as other findings in the literature, have already shown that the PhA can be improved by RT. 26,41 Previous studies also have observed an improvement in inflammatory markers after RT in the same magnitude as reported by Onable-Pearson 24 for TNF-α and Tomeleri et al for IL-6.…”
Section: Discussionsupporting
confidence: 74%
“…28 Thus, because the PhA is a cellular health parameter, it is logical to raise the hypothesis that older adults may realize improvements in inflammatory and oxidative stress markers after a RT intervention, which in turn could be associated with an improvement in PhA. Therefore, the purpose of this investigation was twofold: (a) to determine whether our previous findings that RT improves PhA in older adults 25 would be replicated in a new cohort of older adults; and (b) to investigate whether RT-induced adaptations on inflammatory and oxidative stress biomarkers are related to healthy adaptations in PhA in older women. We hypothesized that RT would promote positive changes in PhA, inflammatory and oxidative stress biomarkers in older women and that these modifications in inflammatory and oxidative stress biomarkers induced by RT would be associated with PhA.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Specifically, promising work has been done to determine the effects of interventions, chiefly resistance training and nutritional support, to minimize sarcopenia and increase muscle function in patients with low PhA. [40][41][42] In conclusion, our findings suggest that in newly diagnosed acute leukemia patients undergoing intensive induction chemotherapy, SPhA technology may provide important prognostic information for TRM and OS. PhA is an objective, repeatable, high-precision measure in acute leukemia patients and, unlike other prognostic factors in this population, is potentially subject to intervention.…”
Section: Discussionmentioning
confidence: 83%
“…A better understanding of the content validity of PhA would allow for stronger evidence to pursue interventions based on the information provided by the measure. Specifically, promising work has been done to determine the effects of interventions, chiefly resistance training and nutritional support, to minimize sarcopenia and increase muscle function in patients with low PhA …”
Section: Discussionmentioning
confidence: 99%